The Chinatown Patient Navigation Program: Adaptation and Implementation of Breast and Cervical Cancer Patient Navigation in Chicago's Chinatown. (April 2019) - Simon, Melissa A; Tom, Laura S; Leung, Ivy; Wong, Esther; Knightly, Eileen E; Vicencio, Daniel P; Yau, Ann; Ortigara, Karen; Dong, XinQi
Background: As health care reform continues within the United States, navigators may play increasingly diverse and vital roles across the health care continuum. The growing interest in patient navigation programs for underserved populations calls for detailed descriptions of intervention components to facilitate implementation and dissemination efforts. Methods: In Chicago's Chinatown, Chinese immigrant women face language, cultural, and access barriers in obtaining breast and cervical cancer screening and follow-up. These barriers spurred the research partnership between Northwestern University, the Chinese American Service League, Mercy Hospital & Medical Center, and Rush University Medical Center to formalize the Chinatown Patient Navigation Collaborative for adapting and implementing previously developed patient navigation models. Results: In this report, we describe the adaptation of patient navigation to build the Chinatown Patient Navigation Collaborative's community-based patient navigation program for breast and cervical cancer. We offer insights into the roles of community patient navigators in safety net hospital and underserved Chinese immigrant communities, and describe implications for patient navigation initiatives to maximize community benefits by improving access to health care for vulnerable populations. Conclusions: Our adaptation and implementation of a patient navigation intervention in Chicago's Chinatown illustrates promising approaches for future navigator research.